Environmental factors affecting sampling success of artificial cover objects - Joppa, Lucas; Williams, C.K.; Casper, G.S.; Temple, S.A. (Herpetological Conservation and Biology, 2010)
Artificial cover objects (ACOs) can be useful for surveying an area for snake abundance. However, very little is known about the correlation between environmental conditions, time of day, and ACO capture success rates. We studied the effects of time of day, temperature, humidity, wind speed, and sky cover variables in relation to ACO sampling capture rates of two colubrid species, Thamnophis butleri and Thamnophis sirtalis. We found that time of day, temperature, and sky cover best explained capture with a quadratic function of temperature being a significant variable. An optimal temperature of 26°C with increasing cloudiness was found to produce the highest ACO sampling capture rate. these observations provide some of the first quantitative information regarding temporal and environmental correlates of ACO methodology, and may help improve the efficiency of the ACO technique for surveying snake abundance.